EVALUATION OF DRUGS SUPPLY MANAGEMENT IN HEALTH DEPARTMENT OF KABUPATEN CILACAP DISTRICT IN 2008, 2009 AND 2010 - Tiekha Kencanasari; Achmad Fudholi; Satibi Satibi (Faculty of Pharmacy, Universitas Gadjah Mada)
Drugs supply management aims to control the drugs supply and make sure that the drugs in good condition, fairly distributed, and fulfill the types and quantity of the drugs needed by health service. Health department of Cilacap District faced many obstacles in drugs supply management during 2008-2010. Therefore, evaluation of drugs supply management in health department of Kabupaten Cilacap during 2008-2010 certainly needed to make the better drugs supply. The research conducted with observational method using descriptive monitoring. Data were collected retrospectively using data of planning, drugs supply and storage, and drugs consumption in health department of Cilacap District. Indicators that used in the research were indicators that determined by health Department of Indonesia in 2006. Primary data were gathered through interview with 3 groups: policy group, drugs supply group, and drugs consumption group or drugs management. Values of drugs management indicators –based on pedoman supervisi dan evaluasi obat publik dan perbekalan kesehatan were gathered through evaluation. The evaluation results show that in 2008, 2009, 2010, the indicators were not fit with the standard indicator, such as: indicator of drugs’ planning accuracy (147%, 108% and 145%), drugs charge per person in Cilacap District (Rp.1.342, Rp.2.000, Rp.4.615) accuracy level of financing the drugs supply (94,60%, 95,04%, 98,30%), and percentage of financing drugs supply (24,8%, 14,8%, 49%). Indicators that fit with the standard indicators were such as: Level of drugs supply (16, 5, and 7 months), accuracy level of drugs item with DOEN 52,4% during 2008-2010, generic drugs supply (89,6%, 79,1%, 88,2%), accuracy level of drugs distribution 100% during 2008-2010, accuracy level of LPLPO delivery time, drugs supply is fit with the drugs demand (109%, 160%, 167%), and drugs charge per visit per prescription (Rp.7.512, Rp. 8.180, Rp. 7.536). Keywords: Drugs Supply Management, Evaluation, Indicators, Health Department of Kabupaten Cilacap